Sustainability of dermatological offices and clinics: challenges and potential solutions. (31st January 2023) - Niebel, Dennis; Herrmann, Alina; Balzer, Susanne; Hecker, Christina; Koch, Susanne; Luhmann, Esther; Becker‐Weimann, Su Youn; Tischler, Max; Löffler, Christin; Saha, Susanne
Summary: Ongoing high consumption of resources results in exceeding the planetary boundaries. Modern healthcare systems contribute to this problem. To address this issue, this article provides an overview of various aspects of sustainable actions in medical offices and clinics that can also be applied to dermatology. Specific fields of action include energy consumption, structural measures, traffic and mobility, organization including digitalization as well as personnel and evaluation. Moreover, we discuss specific topics such as hygiene and cleansing, dermatosurgery and prescription practices. External treatments and cosmetics are discussed separately as dermatological peculiarities. Finally, we provide information on established initiatives for more sustainable health care in Germany. We aim to encourage critical reappraisal of currently established practices and to stimulate the implementation of sustainable measures.